2017
DOI: 10.7448/ias.20.4.21497
|View full text |Cite
|
Sign up to set email alerts
|

Mental health challenges among adolescents living with HIV

Abstract: Introduction: Mental health is a critical and neglected global health challenge for adolescents infected with HIV. The prevalence of mental and behavioural health issues among HIV-infected adolescents may not be well understood or addressed as the world scales up HIV prevention and treatment for adolescents. The objective of this narrative review is to assess the current literature related to mental health challenges faced by adolescents living with HIV, including access to mental health services, the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
250
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(266 citation statements)
references
References 86 publications
14
250
1
1
Order By: Relevance
“…These findings highlight the need for additional attention to the mental health needs of children and adolescents living with HIV and integration of mental health services into paediatric HIV treatment programmes. While data on the prevalence of MSDs among children and adolescents living with HIV in LMICs are limited, research indicates that children and adolescents living with HIV experience increased risk of MSDs compared to non‐infected peers . Similar to adults, MSDs among children and adolescents are associated with suboptimal HIV treatment outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the need for additional attention to the mental health needs of children and adolescents living with HIV and integration of mental health services into paediatric HIV treatment programmes. While data on the prevalence of MSDs among children and adolescents living with HIV in LMICs are limited, research indicates that children and adolescents living with HIV experience increased risk of MSDs compared to non‐infected peers . Similar to adults, MSDs among children and adolescents are associated with suboptimal HIV treatment outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety change over time and studies examining such conditions at a single time point will not represent their course and progression [11]. Although an overwhelming majority of cross-sectional studies have demonstrated the prevalence and related factors of depression and anxiety among people living with HIV, the results have been fragmentary and inconsistent [12][13][14][15]. Findings of the few existing longitudinal studies have also been mixed [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This review is subject to the following limitations: 1) key population groups such as LGTBQI, sex workers and injecting drug users were excluded, as their lived experiences are likely to be different given the higher levels of stigma they possibly encounter relative to the general population of YPL-HIV [149][150][151]; 2) several applicable regional conferences lack online abstract and thus our review may have missed potentially relevant material; 3) our review focused only on YPLHIV in SSA and thus findings may not be generalisable to other regions. However, results from recent studies suggest that there are similarities between YPLHIV in SSA and other developing nations within the South-East Asia Region and Region of the Americas in terms of correlates of mental illness [81,152] and adherence [153,154]. Hence, results could be relevant to settings with similar disease and socioeconomic profiles.…”
Section: Discussionmentioning
confidence: 99%